Comparative Study on Cross-Cultural Teaching Strategies in EFL Classrooms: Indonesia and Thailand Contexts - Ike Dian Puspita Sari; Nurcholis Sunuyeko; Abdul Haviz Hiley; Mohamad Zain Musa; Latipun; Samrit Yossomsakdi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
In the study of phonology, learners examine the distinct characteristics of English sound systems that set it apart from other linguistic structures. This includes an exploration of phonetics, specifically focusing on the mechanics of phonetic articulation and the resulting sounds. This study utilized a quasi-experimental research design involving 62 Thai students as the primary subjects. These participants were organized into two distinct groups: the Experimental Group (EG) and the Control Group (CG). In the contemporary era, technological tools are increasingly leveraged to bolster the educational process. True learning is realized when students can actively engage, communicate, and interact in a manner that aligns with their personal goals and capabilities. With widespread internet access, students can now retrieve information rapidly. Furthermore, they frequently utilize advanced mobile features to share knowledge with their peers. Driven by these trends, this research investigates the efficacy of virtual media in instructing pronunciation to native Thai speakers studying English as a Foreign Language (EFL) at Lukmanul Hakeem private school in Thailand